Novel Image Mosaicking of UAV’s Imagery using Collinearity Condition - Martinus Edwin Tjahjadi; Fourry Handoko; Silvester Sari Sai (International Journal of Electrical and Computer Engineering (IJECE), 2017)
This paper presents a preliminary result of ongoing research on unmanned aerial vehicle (UAV) for cooperative mapping to support a large-scale urban city mapping, in Malang, Indonesia. A small UAV can carry an embedded camera which can continuously take pictures of landscapes. A convenient way of monitoring landscape changes might be through accessing a sequence of images. However, since the camera’s field of view is always smaller than human eye’s field of view, the need to combine aerial pictures into a single mosaic is eminent. Through mosaics, a more complete view of the scene can be accessed and analyzed. A semi-automated generation of mosaics is investigated using a photogrammetric approach, namely a perspective projection which is based on collinearity condition. This paper reviews the general projection model based on collinearity condition and uses that to determine a common projective plane from images. The overlapped points for each RGB channel are interpolated onto that of orthographic plane to generate mosaics. An initial attempt shows a promising result.